Blue humanities storied waterscapes in the anthropocene - Oppermann, Serpil 1959-; Oppermann, Serpil 1959- (Cambridge elements, 2023)
"By drawing on oceanography (marine sciences) and limnology (freshwater sciences), social sciences, and the environmental humanities, the field of the blue humanities critically examines the planet's troubled seas and distressed freshwaters from various socio-cultural, literary, historical, aesthetic, ethical, and theoretical perspectives"-- Provided by publisher